Revealing Demand for Nature Experience Using Purchase Data of Equipment and Lodging - Erling Røed Larsen (Statistics Norway, Research Department, 2001)
In 1967, John Krutilla suggested a relationship between car camping, canoe cruising, and cross-country skiing and induced demand for wild, primitive, and wilderness-related opportunities. Here, the time trend of cross-section parameter estimates of the relationship is examined. Households produce nature experiences using two factors: nature attributes and tools. Tools are equipment and lodging. While many studies have investigated to-site costs of producing nature experiences, on-site costs such as equipment and lodging are studied here by using Consumer Expenditure Survey data for Norway. Income coefficients of household demand for nature services in independent cross-section samples for each year are estimated over the period 1986-95. Proportions of households with non-zero purchase expenditures for equipment are followed from 1975 to 1995. Similar proportions of lodging expenditures are studied from 1986 to 1995. Out of a total of 526 goods in an exhaustive system, 20 goods are singled out and classified as nature experience tools. Two additional non-good expenses are added. Coefficients of demand are estimated for each year by using a tobit structure and a maximum likelihood procedure. While income coefficients of equipment and lodging are quite stable, household size coefficients are not. Both equipment and lodging remain luxury items over the period 1986-1995. Proportions of households with positive purchase expenditure on tools increase over time: In a referendum-by-wallets, nature experience production has received more votes and become more popular.
Keywords: C21; C24; D11; D12; D13; Q21; Q26; 330; Consumption pattern; environmental valuation; experience production; demand for nature services; willingness-to-pay